2019
DOI: 10.1097/crd.0000000000000205
|View full text |Cite
|
Sign up to set email alerts
|

Patent Foramen Ovale and Hypoxemia

Abstract: Patent foramen ovale (PFO), an embryonic remnant of the fetal circulation, is present in 20-25% of adults. Although recent observational studies and clinical trials have established the link between PFO-mediated right-to-left shunting with cryptogenic stroke and migraine with aura, the role of a PFO in exacerbating hypoxemic medical conditions (ie, sleep apnea, chronic obstructive pulmonary disease, pulmonary hypertension, platypnea-orthodeoxia, pulmonary arteriovenous malformation, high-altitude pulmonary ede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 74 publications
0
45
0
2
Order By: Relevance
“…Transient hypoxic episodes—which occur when deoxygenated venous blood enters and combines with oxygenated arterial blood via the RLS—may also explain the mechanism of association between migraine and RLS (Mojadidi et al, ; Tobis & Azarbal, ). Moreover, hypoxemia has also been shown to be a potential trigger of CSD (Hildick‐Smith & Williams, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transient hypoxic episodes—which occur when deoxygenated venous blood enters and combines with oxygenated arterial blood via the RLS—may also explain the mechanism of association between migraine and RLS (Mojadidi et al, ; Tobis & Azarbal, ). Moreover, hypoxemia has also been shown to be a potential trigger of CSD (Hildick‐Smith & Williams, ).…”
Section: Discussionmentioning
confidence: 99%
“…Transient hypoxic episodes-which occur when deoxygenated venous blood enters and combines with oxygenated arterial blood via the RLS-may also explain the mechanism of association between migraine and RLS (Mojadidi et al, 2019; (Gupta, 2004;Wahl et al, 2010). In recent years, a meta-analysis of randomized clinical trials-including three trials consisting of 448 total patients (average follow-up of 10 months)-has shown that between the PFO closure and control groups, there was no significant difference among subjects who experienced a complete cessation of migraine attacks.…”
Section: Ta B L Ementioning
confidence: 99%
“…An independent risk factor for ischemic stroke, it is present in nearly half of all cryptogenic ischemic strokes in a young population 157 . Putative mechanisms by which PFO predispose to stroke risk include: (1) providing a channel from venous to arterial circulation for paradoxical emboli; (2) providing a nidus for in situ thrombus formation; (3) allowing vasoactive substances such as biogenic amines (eg, serotonin, which causes vasoconstriction and platelet aggregation) to bypass pulmonary filtration; and (4) shunting deoxygenated venous blood into the cerebral circulation, where it increases plasminogen activator inhibitor‐1 thereby decreasing fibrinolysis 158,159 . It has been theorized that large PFO size, presence of right‐to‐left shunt at rest, and presence of hypermobile atrial septum are markers of heightened risk of PFO‐related cryptogenic stroke, but studies have not confirmed this 160,161 …”
Section: Potential Mechanisms Of Migraine‐related Strokementioning
confidence: 99%
“…Most of the cases with PFO are patients with additional pulmonary diseases such as chronic lung disease and pneumonectomy. Closure in POS could be considered in cases of severe symptomatic hypoxia in the absence of pulmonary hypertension (Mojadidi et al 2019;Shah et al 2016). In divers, albeit the incidence of decompression sickness is rare, the presence of PFO could cause venous bubbles to go into the arterial circulation and lead to cerebral or myocardial infarction.…”
Section: Indications For Transcatheter Closurementioning
confidence: 99%